Strategi Kepemimpinan Kepala Sekolah dalam Digitalisasi Pembelajaran: Kajian Sistematis - Nurwahyuni, Sari; Mustiningsih; Teguh Triwiyanto (Universitas Sarjanawiyata Tamansiswa, 2025)
In the rapidly evolving era of digital transformation, education faces both challenges and opportunities in integrating technology into the learning process. The role of school principals is a key factor in supporting the success of educational digitalization. This article presents a Systematic Literature Review (SLR) on school leadership strategies in implementing digital learning. The review focuses on identifying effective leadership strategies, the application of transformational leadership models, the challenges faced, and their impact on the effectiveness of technology-based learning. This study employs the SLR method through systematic stages of searching, selecting, and analyzing 45 relevant scholarly articles obtained from databases such as Scopus, Web of Science, Google Scholar, and Garuda, published between 2015 and 2023. The findings reveal that strategies emphasizing the enhancement of teachers’ digital capacity, the development of a collaborative culture, and the adoption of adaptive transformational leadership approaches significantly influence the success of digital learning implementation. Common challenges include limited infrastructure, low digital literacy among educators, and resistance to change. These findings contribute both theoretically and practically to the development of a digital leadership framework aligned with 21st-century educational needs and can serve as a reference for policymakers and education practitioners.